Utformning av ändstationer för automatbana mellan Luleå Centrum och bostadsområdet Kronan - Frykberg, Emil (2013)
This master thesis deals with the conceptual design of end stations to a proposed automatic train ride between Luleå city and the residential area Kronan in Luleå. Public transport is a thing for the future and working systems is a requirement when new cities are built. Today’s public transport need large subsidies from taxpayers and many system carries only a fraction of their costs. NoWait Transit AB and ReRail AB possesses a new train concept that are considered to be cheaper, more environmentally friendly and with a lowered maintenance. The thesis started with an analysis of the companies and Luleå municipality current status, giving a better understanding of the NoWait train concept, which is a new concept based on continuous operation like an escalator. This is made possible by turning the cars almost 90° angle when entering the station to reduce the speed to one-tenth and let the passengers get on and off at a low speed. The track is built above existing infrastructure with lightweight structures and standard components to reduce cost and time of the construction. The propulsion of the cars is coming from linear motors placed along the track which reduces maintenance and energy consumption compared to a regular subway system. An analysis of competitors and similar system was also conducted, giving a better understanding of rapid transit systems, driverless metros and the difference between regular train systems and NoWait’s train system. Based on the initial analyzes and together with the companies, a product specification was created to specify the criteria for the stations. To adapt the NoWait system to a smaller city like Luleå the continuous operation were cancelled and instead letting the train go back and forth between the stations with a small pause at each station. Other examples of criteria were: Unmanned stations, allow protection from bad weather conditions and cars and platform at the same height. When the first part of the product specification process was finished three early station ...